Amicus Curiae: in the 2024 PHPU Presidential Election Session - Wijaya, Dion Untung; Manurung, Agustinus; Tamara, Yogi Angistya; Mijan; Muslim, Thariq; Wiradirja, Hj. Imas Rosidawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the role of the amicus curiae in the 2024 Presidential Election Results Dispute (PHPU) trial in Indonesia. Through a qualitative approach, this research analyzes the contribution of the amicus curiae's independent views to the final decision of the Constitutional Court (MK) and public trust in the fairness of the legal process. Data was collected through document analysis, interviews and direct observation of the trial process. The findings show that amicus curiae has an important role in bringing a neutral and in-depth legal perspective, enriching legal discussions in the courtroom, and strengthening the legitimacy of the Constitutional Court's decisions in the eyes of the public. Despite being faced with various challenges, including political pressure and the complexity of legal cases, the amicus curiae remains consistent in maintaining its legal neutrality and independence